Influence of Geocomposite Properties on the Crack Propagation and Interlayer Bonding of Asphalt Pavements - Sara Spadoni (Materials, 2021)
The application of geocomposites as reinforcement in asphalt pavements is a promising solution for the maintenance/rehabilitation of existing pavements and for the construction of new pavements, whose effectiveness strongly depends on the physical and mechanical properties of the geocomposite. This study aims at assessing the influence of four different geocomposites, obtained by combining a reinforcing geosynthetic with a bituminous membrane, on the crack propagation and interlayer bonding of asphalt pavements. First, a laboratory investigation was carried out on double-layered asphalt specimens. The crack propagation resistance under static and dynamic loads was investigated through three-point bending tests (carried out on specimens with and without notch) and reflective cracking tests respectively, whereas the interlayer shear strength was evaluated through Leutner tests. Then, a trial section was constructed along an Italian motorway and a Falling Weight Deflectometer (FWD) testing campaign was carried out. The laboratory investigation highlighted that—as compared to the unreinforced system—the geocomposites increased the crack propagation energy in the layer above the reinforcement from five to ten times, indicating that they can significantly extend the service life of the pavement by delaying bottom-up and reflective cracking. However, they also worsened the interlayer bonding between the asphalt layers (de-bonding effect). The field investigation indicated that all geocomposites decreased the stiffness of the asphalt layers with respect to the unreinforced pavement as a consequence of the de-bonding effect, thus corroborating the laboratory results. Based on the results obtained, it is desirable that the geocomposite possess a high energy dissipation capability and an upper coating ensuring good adhesion between the asphalt layers. The monitoring of the existing trial section in the future will provide useful data on the long-term field performance of reinforced pavements subjected to actual motorway traffic.